Kingdom of the Netherlands-Netherlands : Selected Issues-Cyclically Advanced Euro-Area Economies; Consequences and Policy Options. (IMF Staff Country Reports; Country Report ;, 2001)
Although the advent of the single currency has generated many advantages for the smaller economies of the euro area, it has raised the possibility that both the amplitude and the duration of cycles in these countries will prove greater than in the past. In the absence of country-specific monetary instruments, discretionary fiscal policy is the only macroeconomic instrument available for influencing aggregate demand in the short term. A business cycle boom may provide a desirable medium-term fiscal position with little risk to growth.